Biodegradable elastomeric networks with exceptional shape memory response under physiological temperature stimuli - Yoo, Dong-Yeop; Han, Joon Soo; Hwang, Seung Sang; Lee, Jung-Hyun; Lee, Albert S. (Pergamon Press Ltd., 2025)
Stimuli-responsive and resilient shape memory polymers (SMPs) were developed to meet burgeoning demands for biomedical applications requiring biodegradable, shape-memory properties with elasticity. However, few studies have been carried out to engineer tunable mechanical properties into SMPs, which are crucial factors for wide applicability. In this study, a series of polyurethane-based elastomer networks derived cross-linked acrylateterminated tri-block copolymers (BCPs) with varying internal block segment and block weight fraction with polycaprolactone were synthesized and their chemical, physical, surface, and shape-memory properties were characterized and good mechanical property (break strain > 2000 %), reversible shape-memory properties were observed. The strategy reported herein with tailorable hydrophilicity / hydrophobicity and mechanical property can be leveraged to boost the development of stimuli-responsive polymers and smart materials for future biomedical applications.